Global progress toward the elimination of active trachoma: an analysis of 38 countries. Issue 4 (April 2022) - Renneker, Kristen K; Abdala, Mariamo; Addy, James; Al-Khatib, Tawfik; Amer, Khaled; Badiane, Mouctar Dieng; Batcho, Wilfrid; Bella, Lucienne; Bougouma, Clarisse; Bucumi, Victor; Chisenga, Tina; Dat, Tran Minh; et al.
Summary: Background: Global elimination of trachoma as a public health problem was targeted for 2020. We reviewed progress towards the elimination of active trachoma by country and geographical group. Methods: In this retrospective analysis of national survey and implementation data, all countries ever known to be endemic for trachoma that had either implemented at least one trachoma impact survey shown in the publicly available Trachoma Atlas, or are in Africa were invited to participate in this study. Scale-up was described according to the number of known endemic implementation units and mass drug administration implementation over time. The prevalence of active trachoma—follicular among children aged 1–9 years (TF1–9 ) from baseline, impact, and surveillance surveys was categorised and used to show programme progress towards reaching the elimination threshold (TF1–9 <5%) using dot maps, spaghetti plots, and boxplots. Findings: We included data until Nov 10, 2021, for 38 countries, representing 2097 ever-endemic implementation units. Of these, 1923 (91·7%) have had mass drug administration. Of 1731 implementation units with a trachoma impact survey, the prevalence of TF1–9 had reduced by at least 50% in 1465 (84·6%) implementation units and 1182 (56·4%) of 2097 ever-endemic implementation units had reached the elimination threshold. 2 years after reaching a TF1–9 prevalence below 5%, most implementation units sustained this target; however, 58 (56·3%) of 103 implementation units in Ethiopia showed recrudescence. Interpretation: Global elimination of trachoma as a public health problem by 2020 was not possible, but this finding masks the great progress achieved. Implementation units in high baseline categories and recrudescent TF1–9 might prolong the attainment of elimination of active trachoma. Elimination is delayed but, with an understanding of the patterns and timelines to reaching elimination targets and a commitment toward meeting future targets, global elimination can still be achieved by 2030. Funding: None.